Direct antecedents of collaborative learning in open online flexible distance learning for higher education students - Mohamad, Liana; Osman, Zahir; Sugilar, S; Nurhayati, Suci (Asian Journal of Contemporary Education, 2025)
This study explores the acceptance of collaborative learning among learners in online flexible distance learning environments. This study examines the direct effects of interaction with peers and tutors, social media usage, learners' self-efficacy, and social presence on collaborative learning. The study employed a survey-based data collection technique, distributing questionnaires and 388 were deemed suitable for the analysis. The data were analysed using structural equation modeling (SEM) with SmartPLS4 software to assess the relationships and test the hypotheses. Hypotheses testing revealed that while interaction with peers and social presence did not significantly influence collaborative learning, tutor interaction, learners' self-efficacy, and social media usage had significant positive effects on collaborative learning. These results suggest that future studies should investigate the underlying reasons for the non-significant impact of peer interaction and social presence, possibly by examining different technological tools or pedagogical approaches. The study's implications extend to educational policymakers and practitioners. It recommends targeted interventions to build student self-efficacy and integrate social media effectively within the learning process. Institutions can create more engaging and successful collaborative learning environments, ultimately fostering improved academic performance and student satisfaction in online flexible distance learning.